Factorial Validation and Psychometric Properties Establishment of Malay Version Critical Care Family Need Inventory - TK, Dharmalingam; MR, Kamaluddin; SK, Hassan (IIUM Medical Journal Malaysia, 2016)
Introduction: Despite general acknowledgement of the importance in assessing family needs in critical care patients, there is no psychometric instrument to measure the family needs within Malaysian settings. This study aimed to perform factorial validation and establish psychometric properties of Malay translated Critical Care Family Need Inventory (CCFNI-M) for Malaysians. Methods: This study consisted of four protocols: Forward-Backward translation, validity, internal reliability and inter domain correlations phases. The factorial validation of the CCFNI-M was based on its administration to 109 family members of critical care patients admitted to the Intensive Care Unit of Hospital Universiti Sains Malaysia, Kelantan, Malaysia. At validity phase, factorial validation was performed using Exploratory Factor Analysis using Principal Component Analysis with Varimax rotation. The internal consistency and inter domain correlations were calculated using Cronbach’s alpha and Pearson correlation coefficient respectively. Results: Preliminary analyses reported the suitability of data for factorial validation. With reference to the original CCFNI, five factors were extracted which explained 49.4% of the total variance. After removal of several items for different reasons, the final items in CCFNI-M were 42. The internal consistency values for five dimensions ranged from 0.72 to 0.87 with inter domain correlation values (r) among the dimensions ranged between 0.36 and 0.61. Conclusion: The high measures of factorial validity, internal consistency and inter domain correlations values of the CCFNI-M make it suitable measure for assessing the family needs of critical care patients.